Performance Expectancy, Self-Efficacy, and Behavioral Intention: Enhancing College Students' Digital Literacy - Setiawan, Ananda; Atmono, Dwi; Rahmattullah, Muhammad; Putri, Rizky Febriyani; Norma, Norma; Wati, Noor Laila (Journal of Economics Education and Entrepreneurship, 2024)
This study aims to determine how the influence of Performance Expectancy, Self-Efficacy, and Behavioral Intention of students on Digital Literacy in the digitalization era. This study is described using a quantitative method with SEM-PLS to determine the phenomenon studied by the decision questionnaire from the questionnaire that has been used in previous studies. The questionnaire was filled out by 355 students of Lambung Mangkurat University. The study showed that Self-Efficacy, Performance Expectancy, and Behavioral Intention have a positive and significant impact on students' Digital Literacy. Self-Efficacy has a positive impact on students' Performance Expectancy. Furthermore, Performance Expectancy also has a positive impact on Behavioral Intention. This is an initial step for universities and students to realize that the presence of digital technology is very necessary in learning in the current digitalization era.